Non-Specific Means of Medical Protection Against COVID-19 - T. E. Sizikova; E. V. Lebedinskaya; O. V. Chukhralya; A. A. Petrov; V. N. Lebedev; S. V. Borisevich (Антибиотики и Химиотерапия)
At the beginning of 2020, humanity faced the pandemic of a novel coronavirus infection – COVID-19. The disease has become one of the most contagious for the entire history of mankind. Among medical means of protection, which can be used for prophylactics and treatment of COVID-19, non-specific medical medical protection means play an important role. The aim of this work is to analyze and evaluate the effectiveness of non-specific medical protection means against COVID-19. These medications are divided in two groups in accordance with the targets of their actions. The medications of the first group either block the virus from entering the cell, or inhibit the enzymes involved in viral RNA replication. The other group of medications affects the immune system of a macroorganism, which plays a crucial role in infection resistance, or blocks inflammatory processes in the lungs. Favipiravir is an example of a broad-spectrum antiviral drug with an established activity against SARS-CoV-2 in particular. During the development of new non-specific medical protection means against COVID-19, a comprehensive validation in representative randomized clinical trials is an important condition for their implementation in medical practice.